Potentiality of Neglected and Underutilized Species (NUS) as a future resilient food: A systematic review - Mohammad Samiul Ahsan Talucder; Umama Begum Ruba; Md. Abu Sayed Robi (Journal of Agriculture and Food Research, 2024)
Food security is still a significant challenge in developing and emerging countries, and sustainable foods are currently in demand. Considering the significance of future smart and sustainable foods, neglected and underutilized species are the best choice for a rapid global population, particularly in developing and poor countries. Considering the urgency of food security and value addition to the Sustainable Development Goal of Zero Hunger, the systematic review aims to give an overview of the potentialities of neglected and underutilized species following a PRISMA framework. The articles were collected from Scopus, PubMed, Web of Science, and google scholar databases. For the collection of published articles, the keywords “Neglected species,” '' Underutilized species,” “Neglected and Underutilized plants,” “SDG and Underutilized plants,” and “NUS and Food security” were entered. 134 articles were selected that were published from 2000 to 2022 following the PRISMA method. The species diversity and their respective geographical location were shortlisted, revealing that most of the articles were published between 2019 and 2022, indicating the increased demand for the potentialities of NUS. The shortlisted articles were approved for systematic review in the context of nutrition and safe food security, medicinal value and safe food accessibility, sustainable production and resilience, small-scale producers' income generation, and genetic diversity maintenance. The aspects have unveiled that NUS is a valuable asset in achieving the target of zero hunger. The species diversity revealed that most documented NUS are studied or researched from Asia's developing and poor countries, followed by Africa. NUS are exposed to hindrances as they are poorly highlighted in the mainstream ground of Sustainable Development Goals. Hence, key strategies must be undertaken to develop their utilization and integration into current agricultural practice. Thus, NUS can widen the prospect of becoming a future resilient food.